Human oocyte calcium analysis predicts the response to assisted oocyte activation in patients experiencing fertilization failure after ICSI. Issue 3 (10th January 2018) - Ferrer-Buitrago, M; Dhaenens, L; Lu, Y; Bonte, D; Vanden Meerschaut, F; De Sutter, P; Leybaert, L; Heindryckx, B
Abstract: STUDY QUESTION: Can human oocyte calcium analysis predict fertilization success after assisted oocyte activation (AOA) in patients experiencing fertilization failure after ICSI? SUMMARY ANSWER: ICSI-AOA restores the fertilization rate only in patients displaying abnormal Ca 2+ oscillations during human oocyte activation. WHAT IS KNOWN ALREADY: Patients capable of activating mouse oocytes and who showed abnormal Ca 2+ profiles after mouse oocyte Ca 2+ analysis (M-OCA), have variable responses to ICSI-AOA. It remains unsettled whether human oocyte Ca 2+ analysis (H-OCA) would yield an improved accuracy to predict fertilization success after ICSI-AOA. STUDY DESIGN, SIZE, DURATION: Sperm activation potential was first evaluated by MOAT. Subsequently, Ca 2+ oscillatory patterns were determined with sperm from patients showing moderate to normal activation potential based on the capacity of human sperm to generate Ca 2+ responses upon microinjection in mouse and human oocytes. Altogether, this study includes a total of 255 mouse and 122 human oocytes. M-OCA was performed with 16 different sperm samples before undergoing ICSI-AOA treatment. H-OCA was performed for 11 patients who finally underwent ICSI-AOA treatment. The diagnostic accuracy to predict fertilization success was calculated based on the response to ICSI-AOA. PARTICIPANTS/MATERIALS, SETTING, METHODS: Patients experiencing low or total failed fertilization after conventional ICSI were included in the study. All participants showed moderate to high rates of activation after MOAT. Metaphase II (MII) oocytes from B6D2F1 mice were used for M-OCA. Control fertile sperm samples were used to obtain a reference Ca 2+ oscillation profile elicited in human oocytes. Donated human oocytes, non-suitable for IVF treatments, were collected and vitrified at MII stage for further analysis by H-OCA. MAIN RESULTS AND THE ROLE OF CHANCE: M-OCA and H-OCA predicted the response to ICSI-AOA in 8 out of 11 (73%) patients. Compared to M-OCA, H-OCA detected the presence of sperm activation deficiencies with greater sensitivity (75 vs 100%, respectively). ICSI-AOA never showed benefit to overcome fertilization failure in patients showing normal capacity to generate Ca 2+ oscillations in H-OCA and was likely to be beneficial in cases displaying abnormal H-OCA Ca 2+ oscillations patterns. LIMITATIONS, REASONS FOR CAUTION: The scarce availability of human oocytes donated for research purposes is a limiting factor to perform H-OCA. Ca 2+ imaging requires specific equipment to monitor fluorescence changes over time. WIDER IMPLICATIONS OF THE FINDINGS: H-OCA is a sensitive test to diagnose gamete-linked fertilization failure. H-OCA allows treatment counseling for couples experiencing ICSI failures to either undergo ICSI-AOA or to participate in gamete donation programs. The present data provide an important template of the Ca 2+ signature observed during human fertilization in cases with normal, low and failed fertilization after conventional ICSI. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the Flemish fund for scientific research (FWO-Vlaanderen, G060615N). The authors have no conflict of interest to declare.